2020
DOI: 10.1186/s12888-020-02891-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum uric acid levels with suicide risk in female patients with major depressive disorder: a comparative cross-sectional study

Abstract: Background Individuals with major depressive disorder (MDD) have a high suicide risk. Some evidence suggests that uric acid (UA) may be involved in the pathophysiology of MDD. The purpose of this study was to evaluate whether serum UA levels were associated with suicide risk in MDD patients. Methods One hundred four female patients with MDD (52 patients with suicide risk and 52 patients without suicide risk) and 52 healthy individual… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…The suicide risk section scores ranged from 0 to 33. As in our previous study, patients with a score <6 were classified as having non-suicidal risk, and those with a score ≥6 were classified as having suicidal risk ( 9 ), which includes suicide ideation, suicide act, or both. The 17-item Hamilton Depression Rating Scale (HAMD-17) was used to assess the severity of depressive symptoms ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The suicide risk section scores ranged from 0 to 33. As in our previous study, patients with a score <6 were classified as having non-suicidal risk, and those with a score ≥6 were classified as having suicidal risk ( 9 ), which includes suicide ideation, suicide act, or both. The 17-item Hamilton Depression Rating Scale (HAMD-17) was used to assess the severity of depressive symptoms ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies on factors leading to suicide have been undertaken for decades. The dimensions include but are not limited to genes, neuroanatomy, biochemistry, the environment, nutrition, physical and mental diseases, mainly depression, and alcohol abuse ( 2 , 5 9 ), but suicide prevention remains an area of uncertainty and needs further research ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…All serum samples were obtained from the consenting volunteers. A smoker was defined as an individual who smoked either daily or occasionally in the 1 month preceding the time of survey [ 34 ]. Alcoholic consumption is often defined by whether or not drinking in the past year or six months or one month [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…A previous study has suggested that uric acid levels are negatively associated with depressive symptoms, anxiety symptoms, and symptom duration 15 . Lower uric acid levels are also related to other psychiatric symptoms, such as higher suicide risk 23 . In the current study, the prevalence of depressive symptoms was signi cantly higher in women with relatively lower uric acid levels than in those with high uric acid levels.…”
Section: Discussionmentioning
confidence: 99%